Social inclusion for children with hearing loss in listening and spoken Language early intervention: an exploratory study - Constantinescu-Sharpe, Gabriella; Phillips, R; Hogan, Anthony; Dornan, Dimity; Davis, Aleisha; Phillips, Rebecca (My University, 2017)
Background: Social inclusion is a common focus of listening and spoken language (LSL) early intervention for children with hearing loss. This exploratory study compared the social inclusion of young children with hearing loss educated using a listening and spoken language approach with population data. Methods: A framework for understanding the scope of social inclusion is presented in the Background. This framework guided the use of a shortened, modified version of the Longitudinal Study of Australian Children (LSAC) to measure two of the five facets of social inclusion (‘education’ and‘interacting with society and fulfilling social goals’). The survey was completed by parents of children with hearing loss aged 4–5 years who were educated using a LSL approach n = 78; 37% who responded). These responses were compared to those obtained for typical hearing children in the LSAC dataset (n = 3265). Results: Analyses revealed that most children with hearing loss had comparable outcomes to those with typical hearing on the ‘education’ and ‘interacting with society and fulfilling social roles’ facets of social inclusion. Conclusions: These exploratory findings are positive and warrant further investigation across all five facets of the framework to identify which factors influence social inclusion.
BMC Pediatrics
Keywords: Children -- Early childhood; Health -- Medical conditions; Child Development -- Speech and Language; Life Events -- Resilience and Adversity; Disadvantage, adversity and resilience; Childhood and child development; Health and wellbeing; Life Events; Children; Health; Child Development; Resilience and Adversity; Early childhood; Medical conditions; Speech and Language; Adversity and resilience; Childhood and child development; Health and wellbeing; Dsiadvantage, adversity and resilience